Shaping futures of prison inmates and former prisoners via higher education: A conceptual study on social return on investment assessment for stakeholders - Santhi Raghavan; Tuan Fatma Tuan Sulaiman; Bibi Nabi Ahmad Khan; Jamil Ramly (2019)
Companies largely play a role in corporate social responsibility (CSR) programmes by engaging with stakeholders including employees, customers, investors, communities and suppliers for financial, environmental and/or social impacts. Contribution quantum is rarely assessed or calculated when it concerns CSR as it is explicitly recognised as the willingness of an organisation to contribute to the community within the ethical norms of charity although strategically CSR can increase revenues by decreasing risks and costs. This study highlights the unique contributions of various stakeholders who wish to make positive and sustainable impact on the socially challenged community – the prisoners. One such engagement is the provision of undergraduate and postgraduate programmes for prisoners in selected Malaysian prisons by Open University Malaysia (OUM), with the partnership of the Prisons Department of Malaysia. It is an economic empowerment programme to rehabilitate and educate its inmates and create employment opportunities if and when they are released. Social Return On Investment (SROI) is a method for measuring and communicating values that incorporates social, environmental and economic impacts to stakeholders. It is an accounting of value created by the activities and the contributions that made the activity possible. Results will be expressed in a ratio of total benefits (a sum of all the outcomes) to total investments (a sum of all costs involved). The purpose of this conceptual study is to calculate the ratio of Ringgit Malaysia (RM) of social value created for every RM1 spent on its activities. Inmates who are accepted into OUM’s programmes attend face-to-face tutorials conducted by OUM tutors and sit for examinations in the prison. They are supported by OUM’s online learning management system where they manage their studies, submit their assignments and access the digital library. (Abstract by authors)